Analisis Kemampuan Pemecahan Masalah Matematika Pada Materi Garis Singgung Lingkaran Ditinjau dari Gaya Kognitif - Febrianti Febrianti; Sudi Prayitno; Syahrul Azmi; Arjudin Arjudin (Pendidikan Matematika FKIP Universitas Mataram, 2021)
This study aimed to describe students' ability in solving the tangent of the circle problems based on reflective and impulsive cognitive styles. This type of research was descriptive research. The sampling of this study were 4 students of class VIII-4 SMPN 4 Mataram who consisted of 2 reflective students and 2 impulsive students. Students with reflective cognitive style have a very good level of problem-solving ability. This is shown at the stage of understanding the problem, thinking of a plan, and carrying out the plan have done very well. Meanwhile, students with impulsive cognitive style have a level of problem-solving ability with sufficient and fewer categories. This is shown at the stage of thinking of a plan, carrying out the plan, and at the time of re-examining the results of students' work that they have not been able to do well.